Mitigating environmental impact by development of ambient-cured EAF slag and fly ash blended geopolymer via mix design optimization - Mishra, Anant (2024)
This article discusses the utilization of industrial by-products, namely, electric arc furnace slag (EAFS) and fly ash to produce cementless geopolymer binder. Taguchi-grey optimization is used for experimental design and for investigating the effects of mix design parameters. Fly ash, in the levels of 0-75% (by mass), partly replaced EAFS in the binary-blended composite system. Experiments were performed on the microstructural development, mechanical properties, and durability of ambient-cured EAFS-fly ash geopolymer paste (EFGP). The optimal mix with 75-25% composition of EAFS and fly ash produced ~ 39 MPa compressive strength accrediting to the co-existence of C-A-S-H and N-A-S-H gels. The initial and final setting times were 127 min and 581 min, respectively, owing to adequate alkali and amorphous contents in the matrix, and the flowability was 108% due to sufficient activator content and the spherical shape of fly ash particles. SEM, XRD, and FTIR results corroborated the mechanical test results.